A new alternative revised step-by-step flutter analysis. Issue 196 (January 2020) - Chen, G.F.; Li, Hui; Zhang, Y.Z.
Abstract: A novel revised step-by-step flutter analysis for bridge, based on step-by-step flutter method introduced by Matsumoto, is rewritten in an alternative formulation called simplified revised step-by-step analysis model (SRSBSA). In the SRSBSA model, the expressions are simpler and physical interpretations such as aerodynamic damping can be given. Mathematical proof and numerical examples show that the efficacy and accuracy of the SRSBSA agree well with the revised step-by-step ones and other documented approaches.